Guiding functions of the C-terminal domain of topoisomerase IIα advance mitotic chromosome assembly - Keishi Shintomi (Nature Portfolio, 2021)
Topoisomerase IIα (topo IIα) is critical for mitotic chromatid assembly. Here the authors report a refinement of the mitotic chromatid reconstitution assay and provide novel insights into the C-terminal domain (CTD) of topo IIα.